2020
DOI: 10.1186/s12885-020-07011-z
|View full text |Cite
|
Sign up to set email alerts
|

Whole-brain irradiation with hippocampal sparing and dose escalation on metastases: neurocognitive testing and biological imaging (HIPPORAD) – a phase II prospective randomized multicenter trial (NOA-14, ARO 2015–3, DKTK-ROG)

Abstract: Background: Whole brain radiation therapy (WBRT) is the standard therapy for multiple brain metastases. However, WBRT has a poor local tumor control and is associated with a decline in neurocognitive function (NCF). Aim of this trial is to assess the efficacy and safety of a new treatment method, the WBRT with hippocampus avoidance (HA) combined with the simultaneous integrated boost (SIB) on metastases/resection cavities (HA-WBRT+SIB). Methods: This is a prospective, randomized, two-arm phase II multicenter t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 57 publications
0
31
0
1
Order By: Relevance
“…When WBRT is inevitable, hippocampal avoidance in combination with memantine can also reduce cognitive impairment. 43 , 44 It is worth noting that the addition of EGFR TKI to WBRT does not further increase neurotoxicity according to a systematic review. 45 …”
Section: Discussionmentioning
confidence: 99%
“…When WBRT is inevitable, hippocampal avoidance in combination with memantine can also reduce cognitive impairment. 43 , 44 It is worth noting that the addition of EGFR TKI to WBRT does not further increase neurotoxicity according to a systematic review. 45 …”
Section: Discussionmentioning
confidence: 99%
“…Another clinical trial exploring hippocampal sparing prophylactic cranial irradiation in patients with small-cell lung cancer limited hippocampal D mean to 8 Gy in 10 fractions (5.6 Gy EQD2 α / β = 2) ( 21 ). In the ongoing prospective randomized HIPPORAD trial (NOA-14, ARO 2015-3, DRKS00004598), the hippocampal constraints include D 98% ≤ 9 Gy (6.2 Gy EQD2 α / β = 2), D 2% ≤ 17 Gy (14.5 Gy EQD2 α / β = 2), and an aimed D mean ≤ 10 Gy (7.1 Gy EQD2 α / β = 2) ( 20 ). The equivalent dose applied in our HA-WBRT-cohort was therefore in alignment with these data and could be considered sufficient for neurocognitive protection.…”
Section: Discussionmentioning
confidence: 99%
“…Hippocampal interventions were defined as hippocampal resections or RT to the head with a total mean hippocampal dose (D mean , summed across all RT series) ≥ 3 Gy (equivalent dose delivered in 2 Gy fractions [EQD2, α / β = 2]) and a total maximal hippocampal dose (D max , summed across all RT series) ≥ 14.4 Gy (EQD2, α / β = 2). The thresholds were set taking into consideration the strictest hippocampal constraints imposed in clinical trials ( 10 , 20 , 21 ).…”
Section: Methodsmentioning
confidence: 99%
“…In a propensity score-matched comparison against WBRT, Popp et al reported significantly improved local tumour control rates, intracranial PFS, reduction in neurological deaths and even better OS [ 12 ]. This has led the group to continue to a phase II HIPPORAD Trial comparing HA-WBRT+SIB against WBRT+SIB (German Clinical Trials Registry: DRKS00004598) [ 16 ].…”
Section: Introductionmentioning
confidence: 99%